A Broad Continuum of Aeolian Impact Ripple Morphologies on Mars is Enabled by Low Wind Dynamic Pressures. Issue 10 (10th October 2020) - Sullivan, R.; Kok, J. F.; Katra, I.; Yizhaq, H.
Abstract: Aeolian ripples are common in sandy environments on Earth and Mars. On Earth, ripples in sorted dune sands typically are <1 cm high and are erased in high winds. On Mars in similar sands, ripple wavelengths commonly exceed 2 m, with much smaller ripples superimposed. Large Martian ripple sizes and juxtaposition of multiple wavelengths have raised questions about origins and the applicability of terrestrial aeolian physics to different planetary environments. Here, two hypotheses are evaluated for large Martian ripples: (1) fluid/wind drag, analogous to ripples formed under water on Earth, as proposed previously for Martian large ripples; and (2) saltation impact splash, the mechanism creating aeolian ripples of much smaller size on Earth. This study evaluates these hypotheses with numerical experiments and Mars rover observations, and concludes that large Martian ripples develop through the saltation impact splash mechanism. The low‐density Martian atmosphere enables aeolian impact ripples to grow much higher into the boundary layer before reaching maximum heights constrained by wind dynamic pressure effects at crests. In this concept, boundary layer conditions influence mature ripple heights more directly than wavelengths. On Mars, low wind dynamic pressures, combined with the impact splash mechanism, also help to explain other distinctively Martian aeolian bedforms, including large longitudinal ripples observed by rovers and orbiters, and transverse aeolian ridges (TARs) distributed widely across the Martian surface. Compared with Earth, low wind dynamic pressures on Mars permit a wider range of ripple sizes, relative ages, morphologies, and orientations in close proximity, as displayed in rover observations. Plain Language Summary: On Earth, winds drive sand grains downwind in bouncing motions (called "saltation"). Each high‐energy bounce also splashes other surface grains shorter distances, and this impact splash process creates small, 10 cm wavelength ripples with heights <1 cm in typical dune sands. On Mars, sands with similar grain sizes form much larger ripples with wavelengths exceeding 2 m, and their origins have been debated. In this study, numerical simulations and Mars rover observations indicate that aeolian impact ripples can grow much larger on Mars than on Earth because the thin Martian atmosphere does not interfere with the upward growth of ripple crests until ripples are much higher (which in turn constrains minimum, but not maximum, ripple wavelengths). In this concept, wind conditions influence mature aeolian ripple heights more directly than ripple wavelengths. This concept also helps explain other, distinctively Martian aeolian features including large longitudinal ripples, and large transverse aeolian ridges (TARs) observed widely across the Martian surface. Key Points: On Mars, the saltation impact splash mechanism creates a wider range of aeolian ripple sizes than on Earth Low wind dynamic pressures on Mars allow ripple heights to grow further upward into the boundary layer than on Earth The same mechanism also helps explain other distinctively Martian bedforms: large longitudinal ripples and transverse aeolian ridges (TARs)